M-Polynomial and NM-Polynomial of Used Drugs against Monkeypox - Özge Çolakoğlu; Muhammad Kamran; Ebenezer Bonyah (Journal of Mathematics)
Monkeypox has recently re-emerged. Since monkeypox has started to be seen in many countries without an epidemic, studies have started on new drugs used to treat this disease. Drug discovery is a challenging process. To alleviate this process, molecular descriptors used to predict the physical, chemical, and biological properties of chemical structures are studied. Molecular descriptors are numerical values of a chemical structure represented by a graph. In this study, M-polynomial and neighborhood M-polynomial molecular descriptors of drugs used and candidates for use in monkeypox are calculated and these descriptors are compared.